Successes, Challenges and Recommendations Regarding Using Incentives to Increase Aggregate Fruit and Vegetable Consumption in Elementary Schools - Koehn, Emily; Ramquist, Lucy; Brault, Alex; Leong, Zhi Wen; Kim, Jisu; Douglass, Nicholas; Culbertson, Alaina; Pumper, Jonathan (My University, 2015)
In this study, we partnered with two Western Wisconsin elementary schools (N=420 and N=440) to examine the influence of a variety of group-level incentives on children's aggregate fruit and vegetable consumption during school lunch. We observed and recorded aggregate fruit and vegetable consumption in both schools over an initial baseline period (3 days) followed by an incentive period (6 days/4 days)and a return to baseline period (3 days).
Color poster with text, tables, and images.
Keywords: Posters; Produce consumption; Nutrition; Elementary schoolchildren